Host-specific factors affect the pathogenesis of adverse reaction to metal debris - Lehtovirta, Lari (BMC Musculoskelet Disord, 2019)
BACKGROUND: Adverse Reaction to Metal Debris (ARMD) is a major reason for revision surgeries in patients with metal-on-metal (MoM) hip replacements. Most failures are related to excessively wearing implant producing harmful metal debris (extrinsic factor). As ARMD may also occur in patients with low-wearing implants, it has been suggested that there are differences in host-specific intrinsic factors contributing to the development of ARMD. However, there are no studies that have directly assessed whether the development of ARMD is actually affected by these intrinsic factors. METHODS: We included all 29 patients (out of 33 patients) with sufficient data who had undergone bilateral revision of ASR MoM hips (58 hips) at our institution. Samples of the inflamed synovia and/or pseudotumour were obtained perioperatively and sent to histopathological analysis. Total wear volumes of the implants were assessed. Patients underwent MARS-MRI imaging of the hips preoperatively. Histological findings, imaging findings and total wear volumes between the hips of each patient were compared. RESULTS: The difference in wear volume between the hips was clinically and statistically significant (median difference 15.35 mm(3), range 1 to 39 mm(3), IQR 6 to 23 mm(3)) (p < 0.001). The median ratio of total wear volume between the hips was 2.0 (range 1.09 to 10.0, IQR 1.67 to 3.72). In majority of the histological features and in presence of pseudotumour, there were no differences between the left and right hip of each patient (p > 0.05 for all comparisons). These features included macrophage sheet thickness, perivascular lymphocyte cuff thickness, presence of plasma cells, presence of diffuse lymphocytic infiltration and presence of germinal centers. CONCLUSIONS: Despite the significantly differing amounts of wear (extrinsic factor) seen between the sides, majority of the histological findings were similar in both hips and the presence of pseudotumour was symmetrical in most hips. As a direct consequence, it follows that there must be intrinsic factors which contribute to the symmetry of the findings, ie. the pathogenesis of ARMD, on individual level. This has been hypothesized in the literature but no studies have been conducted to confirm the hypothesis. Further, as the threshold of metal debris needed to develop ARMD appears to be largely variable based on the previous literature, it is likely that there are between-patient differences in these intrinsic factors, ie. the host response to metal debris is individual. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12891-019-2578-0) contains supplementary material, which is available to authorized users.